2017
DOI: 10.1038/s41598-017-14998-2
|View full text |Cite
|
Sign up to set email alerts
|

MiSNPDb: a web-based genomic resources of tropical ecology fruit mango (Mangifera indica L.) for phylogeography and varietal differentiation

Abstract: Mango is one of the most important fruits of tropical ecological region of the world, well known for its nutritive value, aroma and taste. Its world production is >45MT worth >200 billion US dollars. Genomic resources are required for improvement in productivity and management of mango germplasm. There is no web-based genomic resources available for mango. Hence rapid and cost-effective high throughput putative marker discovery is required to develop such resources. RAD-based marker discovery can cater this ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Mango is a tall, evergreen tree belonging to the genus Mangifera of the Anacardiaceae family. It is an important tropical fruit ( Iquebal et al, 2017 ; Lora & Hormaza, 2018 ) that originates in tropical and subtropical regions in Southeast Asia ( Dutta et al, 2013 ; Sherman et al, 2015 ). Owing to its wide range of cultivation ( Bajpai et al, 2016 ), high nutrient value, pleasing appearance, and unique flavor ( Surapaneni et al, 2013 ), it is widely loved by consumers and has the reputation of being known as the “King of Tropical Fruits” ( Khan, Ali & Khan, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mango is a tall, evergreen tree belonging to the genus Mangifera of the Anacardiaceae family. It is an important tropical fruit ( Iquebal et al, 2017 ; Lora & Hormaza, 2018 ) that originates in tropical and subtropical regions in Southeast Asia ( Dutta et al, 2013 ; Sherman et al, 2015 ). Owing to its wide range of cultivation ( Bajpai et al, 2016 ), high nutrient value, pleasing appearance, and unique flavor ( Surapaneni et al, 2013 ), it is widely loved by consumers and has the reputation of being known as the “King of Tropical Fruits” ( Khan, Ali & Khan, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mk, Rk and Ln cultivars showed different flowering (December to January) and fruit maturity (May to July) time 91 . These cultivars are diversely related each other in a study on nucleotide polymorphisms (SNPs) 92 . The genetic background of these cultivars described earlier showed that Rk cultivar grouped in phylogenetic cluster 5 of structure sub-population I, while Ln and Mk cultivars are grouped in phylogenetic cluster 7 of structure sub-population II 93 .…”
Section: Methodsmentioning
confidence: 99%
“…One way to reduce the complexity in GBS is RAD-Seq (restriction-site associated DNA sequencing). Using this technique, 1.25 million SNPs were discovered in a panel of 84 mango varieties and used for development of the genomic resource MiSNPDb [ 21 ]. SNPs are also commonly mined from expressed sequence tag (EST) or transcriptome gene sequences.…”
Section: Genotypingmentioning
confidence: 99%